Molecular characterization of Enterobacteriaceae producing β-lactamase and methicillin-resistant staphylococci isolated from the hospital environment and catheters in two public hospitals in Benin, Republic of Benin - Gbotche, Elodie; DOUGNON, Victorien; MISSIHOUN, ANTOINE ABEL HOUMÈNOU (My University, 2020)
Antimicrobial resistance is a real public health problem. All over the world, it has a considerable impact in hospitals. The present study was conducted to ascertain the bacterial ecology in two hospitals in Benin as well as the resistance genes present in the recovered isolates. A total of 146 environmental and catheter samples were collected at the University Hospital Center of Abomey-Calavi / So-Ava and at the Beninese Army Hospital of Cotonou. These samples were inoculated on Mannitol Salt and Eosin Methylene Blue agars. The colonies obtained were identified and their sensitivity to antibiotics were tested, using the Kirby Bauer technique. Four resistance genes encoding the production of extendedspectrum beta-lactamases (blaCTX-M1, blaCTX-M2, blaCTX-M9, blaCTX-M15) and the gene coding for methicillin resistance (mecA) were screened. The gene coding for methicillin resistance (mecA) was sought in staphylococci. A total of 69 (53,49%) and 60 (46,51%) strains belonging to Enterobacteriaceae family and staphylococci were identified, respectively. A predominance of Staphylococcus aureus (25.6%) followed by Enterobacter cloacae (21.0%) and coagulase negative staphylococci (21.0%) was observed. These bacterial strains showed multidrug-resistance, particularly to beta-lactams, fluoroquinolones, aminoglycosides, and macrolides. Beta-lactamases were identified in the genome of bacterial strains with a predominance of blaCTX-M15 (42.8%). The frequency of the mecA gene in staphylococci was 50%. These results show the magnitude of the antimicrobial resistance situation in the hospitals investigated. They can be used to support advocacy for urgent action at the national level, especially with regards to the management and efficient use of antimicrobials in Benin.
Keywords: Antimicrobial resistance; resistance genes; hospital environment; catheters; Benin.